Enabling growth-decoupled Komagataella phaffii recombinant protein production based on the methanol-free PDH promoter - Bernat-Camps, Núria; Ebner, Katharina; Schusterbauer, Veronika; Fischer, Jasmin Elgin; Nieto-Taype, Miguel Angel; Valero, Francisco; Glieder, Anton; Garcia-Ortega, Xavier (Frontiers in Bioengineering and Biotechnology, 2023)
The current transition towards the circular bioeconomy requires a rational development of biorefineries to sustainably fulfill the present demands. The use of Komagataella phaffii (Pichia pastoris) can meet this challenge, since it has the capability to use crude glycerol as a carbon-source, a by-product from the biodiesel industry, while producing high- and low-added value products. Recombinant protein production (RPP) using K. phaffii has often been driven either by the methanol induced AOX1 promoter (PAOX1) and/or the constitutive GAP promoter (PGAP). In the last years, strong efforts have been focused on developing novel expression systems that expand the toolbox variety of K. phaffii to efficiently produce diverse proteins that requires different strategies. In this work, a study was conducted towards the development of methanol-free expression system based on a heat-shock gene promoter (PDH) using glycerol as sole carbon source. Using this promoter, the recombinant expression is strongly induced in carbon-starving conditions. The classical PGAP was used as a benchmark, taking for both strains the lipase B from Candida antarctica (CalB) as model protein. Titer of CalB expressed under PDH outperformed PGAP controlled expression in shake-flask cultivations when using a slow-release continuous feeding technology, confirming that PDH is induced under pseudo-starving conditions. This increase was also confirmed in fed-batch cultivations. Several optimization rounds were carried out for PDH under different feeding and osmolarity conditions. In all of them the PDH controlled process outperformed the PGAP one in regard to CalB titer. The best PDH approach reached 3.6-fold more specific productivity than PGAP fed-batch at low μ. Compared to the optimum approach for PGAP-based process, the best PDH fed-batch strategy resulted in 2.3-fold higher titer, while the specific productivity was very similar. To summarize, PDH is an inducible promoter that exhibited a non-coupled growth regulation showing high performance, which provides a methanol-free additional solution to the usual growth-coupled systems for RPP. Thus, this novel system emerges as a potential alternative for K. phaffii RPP bioprocess and for revaluing crude glycerol, promoting the transition towards a circular economy.